Use the definition of the natural log:
ln (a) = c means a = e^c.
So here, x = e^y by definition.
2007-04-16 10:42:17
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
Put y = ln(x) (Power e both sides)
e^y = e^ln(x) ( By definition e^ln(x)=x)
So, e^y = x => function f
Discontinuity at asymptote x = 0 on the plane (x,y) (graphic)
Dom f = ] 0, infinity => possible values for x
Ima f = ] 0, infinity => possible values for y
Answer : x => ]0, infinity ( x take only positive values without 0)
2007-04-16 18:34:21
·
answer #2
·
answered by frank 7
·
0⤊
0⤋
take the exponential of y, this will cancel the ln (x)
so ln(x) = y
take exponential
x = exp to the power of y
2007-04-16 17:40:05
·
answer #3
·
answered by wil_hopcyn 2
·
0⤊
0⤋
you raise both sides by e
e^ln(x)=e^y
e^ln cancels out leaving you with x=e^y
That's as far as you can go. Good luck!
2007-04-16 17:55:47
·
answer #4
·
answered by beachchic08 2
·
0⤊
0⤋
If you have ln(x) = y, then:
e^[ln(x)] = e^y, or:
x = e^y
where e, the base of the natural logarithm, is equal to 2.71828182845904523536
2007-04-16 17:42:02
·
answer #5
·
answered by Dave_Stark 7
·
0⤊
1⤋